Crime frames and gender differences in the activation of crime concern and crime responses. (January 2020) - de Vries, Ieke; Farrell, Amy; Bouché, Vanessa; Wittmer-Wolfe, Dana E.
Abstract: Prior work has reported mixed evidence for the gender gap in crime concern and crime responses, yet very few studies have considered the importance of the framing of a crime in explaining this gap. Crime frames are important because they can raise deep levels of concern that activate a criminal justice system response to the crime. This study draws on the literature on problem framing to examine gender differences in crime concern and crime responses in relation to human trafficking. Human trafficking is a type of crime that has raised public alarm in the U.S and is being framed by the government and the media as a crime to which women are at increased risk. Using data from a national probability sample of approximately 2000 Americans, the findings show that beliefs about the causes of human trafficking, specifically gender discrimination and transnational crime, are associated with gender differences in concern and activation of the criminal justice system. These findings can guide future research on gender differences in crime concern and crime responses and call for research and policies that are sensitive to gendered effects of framing on public opinion about crime and criminal justice issues.